2006
DOI: 10.1097/mbc.0b013e32801010b7
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol impairs coagulation and fibrinolysis in whole blood: a study performed with rotational thromboelastometry

Abstract: Objective: The objective of the study was to study the effects of ethanol on the coagulation and the fibrinolysis in whole blood. Methods: Blood samples from healthy volunteers were analysed before and after in vitro addition of ethanol in order to achieve ethanol concentrations of 0‰, 1‰, 2‰ and 4‰ respectively (0, 22, 44 and 88 mmol/l). Coagulation and fibrinolysis were then assessed using rotational thromboelastometry. Results: We found that increasing ethanol levels increasingly impaired coagulation as eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…end-concentration of wine, remained unchanged with simultaneous delay in clot formation. This finding is in accordance with previous studies [3,4], and clinically important, since the present guidelines regarding the treatment of traumatic coagulopathy are based on viscoelastic determination of clot strength. However, an attempt to counteract the particular effect of alcohol on clot formation may not be indicated since the developing clot representing combined function of extrinsic coagulation pathway and platelets (EXTEM), will be finally firm enough.…”
Section: Discussionsupporting
confidence: 81%
“…end-concentration of wine, remained unchanged with simultaneous delay in clot formation. This finding is in accordance with previous studies [3,4], and clinically important, since the present guidelines regarding the treatment of traumatic coagulopathy are based on viscoelastic determination of clot strength. However, an attempt to counteract the particular effect of alcohol on clot formation may not be indicated since the developing clot representing combined function of extrinsic coagulation pathway and platelets (EXTEM), will be finally firm enough.…”
Section: Discussionsupporting
confidence: 81%
“…In their comprehensive review of these mechanistic investigations, Salem et al 28 concluded that alcohol appears to impair platelet aggregation, may partially activate and thus impair platelet activation, decreases coagulation factors such as fibrinogen, increases fibrinolysis at moderate doses, and inhibits fibrinolysis at high doses. In a 2006 study using rotational thromboelastometry and whole blood ''spiked'' ex vivo with increasing levels of ethanol, Engstrom et al 29 found that EtOH impaired clot formation (by clot formation time and > angle), with no effect on maximum clot strength. They also noted a profound impairment of fibrinolysis, consistent with prior studies correlating alcohol intake to acute increases in PAI-1 activity.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have assessed the hemostatic properties of ethanol owing to the association between light to moderate alcohol drinking and a lower incidence of ischemic heart disease resulting from suppression of thrombus formation and atherosclerotic progression, and a higher bleeding tendency (Mukamal et al 2003 ). Ethanol inhibits platelet aggregation and impairs fibrinolysis (Marumo and Wakabayashi 2010 ; Engström et al 2006 ; Ehrlich and Humpel 2014 ). The results of studies reporting the impact of ethanol on the coagulation vary according to the experimental conditions and the tests used (Engström et al 2006 ; Bloemen et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol inhibits platelet aggregation and impairs fibrinolysis (Marumo and Wakabayashi 2010 ; Engström et al 2006 ; Ehrlich and Humpel 2014 ). The results of studies reporting the impact of ethanol on the coagulation vary according to the experimental conditions and the tests used (Engström et al 2006 ; Bloemen et al 2012 ). In preliminary tests, we found that ethanol at contents ranging between 0.05 and 0.2 %v/v had no effect on TG parameters either at room temperature or at 37 °C.…”
Section: Discussionmentioning
confidence: 99%